OBSERVED PROPERTIES OF CONTACT BINARY SYSTEMS - Kalimeris, A.; Rovithis-Livaniou, H. (Одеські астрономічні публікації, 2017)
A group of close eclipsing systems, which continues to pose a challenge in many subjects of modern astrophysics, is that of contact binaries. In this study, using the most recent observational data of a large sample of such systems, a review concerning their properties is presented. Except from the basic graphs, appeared so far in similar reviews, some new diagrams for their angular momentum, horizontal energy transfer, and corrected mass-radius relations are given. From them, some new important properties of contact binaries are derived.